2020
DOI: 10.3390/app10238665
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Behaviors of Date Palm Vitroplants Treated with Microbial Consortia and Compost in Response to Salt Stress

Abstract: The main challenge of the agricultural sector is to develop new ecological technologies that increase the yields and the tolerance of crops to abiotic constraints, especially in arid areas. The objective of this study was to test the potential roles of biofertilizers, namely, arbuscular mycorrhizal fungi (AMF), a native AMF consortium (AMF1) and an exotic AMF strain (AMF2); plant growth-promoting rhizobacteria (PGPR); and compost (comp), applied separately or in combination, in improving the tolerance of date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…Various studies have reported the combined synergistic effect of compost, and PGPR in alleviate salinity and drought stress of wheat plants (Kanwal et al, 2017;Yaseen et al, 2020). Similarly, various studies have reported that the dual or triple combination of PGPR, AMF, and compost has a strong ability to mitigate the adverse effects of salinity stress on plant, by enhancing photosynthesis and water status (Bharti et al, 2016: Toubali et al, 2020. They also demonstrated that, in the interactions between plants and AMF, PGPR and compost, benefit each other from this mutualistic association.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported the combined synergistic effect of compost, and PGPR in alleviate salinity and drought stress of wheat plants (Kanwal et al, 2017;Yaseen et al, 2020). Similarly, various studies have reported that the dual or triple combination of PGPR, AMF, and compost has a strong ability to mitigate the adverse effects of salinity stress on plant, by enhancing photosynthesis and water status (Bharti et al, 2016: Toubali et al, 2020. They also demonstrated that, in the interactions between plants and AMF, PGPR and compost, benefit each other from this mutualistic association.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the antioxidant enzymes mainly decreased between 10 and 14 months of cultivation, in the presence of saline stress, where the shoot SOD activity showed the greatest decline (25%) between the two harvests in compost-treated plants (Figures S2 and S3). The significant increase in antioxidant enzyme activity in treated plants in the presence of saline stress after 10 months of cultivation probably led to a significant decrease in stress markers [11,12]. This decrease was more significant after 14 months of cultivation.…”
Section: Stress Markers and Organic Osmolytes Content And Activity Of...mentioning
confidence: 94%
“…AMF-assisted enhancement of the photosynthetic pigment content, such as chlorophyll, has been reported in date palm plants subjected to salinity [81,82]. According to these studies, AMF enhanced the uptake of minerals, especially, Mg which represents the major center of the chlorophyll molecule [65].…”
Section: Salinitymentioning
confidence: 97%
“…Salinity affects the ability of date palm to absorb water due to the osmotic impact and alteration in cell-water relations [76]. Moreover, it exerts a detrimental impact on photosynthetic pigments [80,81]. Several studies, however, found that, when salinity increased, the content of chlorophyll considerably decreased [66,76].…”
Section: Salinitymentioning
confidence: 99%
See 1 more Smart Citation